Effects of Class II-Selective Histone Deacetylase Inhibitor on Neuromuscular Function and Disease Progression in SOD1-ALS Mice. (21st May 2018) - Buonvicino, Daniela; Felici, Roberta; Ranieri, Giuseppe; Caramelli, Riccardo; Lapucci, Andrea; Cavone, Leonardo; Muzzi, Mirko; Di Pietro, Lorena; Bernardini, Camilla; Zwergel, Clemens; Valente, Sergio; Mai, Antonello; et al.
Highlights: Class II HDAC inhibition prompts transient improvement of motor function of ALS mice. Class II HDAC inhibition increases muscle electrical potential of ALS mice. Class II HDAC inhibition sustains myogenic factor expression in muscle of ALS mice. Abstract: Emerging evidence indicates that transcriptome alterations due to epigenetic deregulation concur to ALS pathogenesis. Accordingly, pan-histone deacetylase (HDAC) inhibitors delay ALS development in mice, but these compounds failed when tested in ALS patients. Possibly, lack of selectivity toward specific classes of HDACs weakens the therapeutic effects of pan-HDAC inhibitors. Here, we tested the effects of the HDAC Class II selective inhibitor MC1568 on disease evolution, motor neuron survival as well as skeletal muscle function in SOD1G93A mice. We report that HDACs did not undergo expression changes during disease evolution in isolated motor neurons of adult mice. Conversely, increase in specific Class II HDACs (-4, -5 and -6) occurs in skeletal muscle of mice with severe neuromuscular impairment. Importantly, treatment with MC1568 causes early improvement of motor performances that vanishes at later stages of disease. Notably, motor improvement is not paralleled by reduced motor neuron degeneration but by increased skeletal muscle electrical potentials, reduced activation of mir206/FGFBP1-dependent muscle reinnervation signaling, and increased muscle expression of myogenic genes.